2008
DOI: 10.1007/s12243-007-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

The Italian national electromagnetic field monitoring network

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…The dataset of this publication is impressive but it is unclear whether temporal trends are affected by the underlying heterogeneous dataset, whereas our study used the exact same procedure over the entire study period. Monitoring systems have been implemented in various cities in Europe, such as in Greece (Gotsis et al, 2008), Italy (Troisi et al, 2008) and Portugal (Oliveira et al, 2007). However, no analyses of time trends are available from these measurement networks.…”
Section: Comparison Of Rf-emf Exposure Levels With the Literaturementioning
confidence: 99%
“…The dataset of this publication is impressive but it is unclear whether temporal trends are affected by the underlying heterogeneous dataset, whereas our study used the exact same procedure over the entire study period. Monitoring systems have been implemented in various cities in Europe, such as in Greece (Gotsis et al, 2008), Italy (Troisi et al, 2008) and Portugal (Oliveira et al, 2007). However, no analyses of time trends are available from these measurement networks.…”
Section: Comparison Of Rf-emf Exposure Levels With the Literaturementioning
confidence: 99%
“…Troisi et al [] originally described the Italian network. The My Structured Query Language (MySQL) database [MySQL, ] is the largest database of electric field measurements known to us, containing a total of 50,662,433 lines of measurement data.…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring network comprised three different broadband probe measurement systems. Troisi et al [] reported that a total of 7,719 sites were monitored as follows: schools (2,087), public places (1,370), homes (4,131), and hospitals (131). Average monitoring time per site was 23 days.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mobile systems are an unavoidable part of modern life and cannot be easily removed or replaced. For these reasons, an objective assessment of the human exposure to the radio frequency (RF) electromagnetic radiation is of great importance [1][2][3][4][5][6][7][8][9]. Furthermore, exposure to RF electromagnetic field should be continuously monitored because of expected tremendous growth of traffic in future wireless networks [10] and dense implementation of small cells with base station installed closer to users [11].…”
Section: Introductionmentioning
confidence: 99%